Psychometric validation of the Chinese version of the Adolescent Asthma Self-Efficacy Questionnaire - Wang, Yuanyuan; Chen, Hongyu; Cao, Jinjin; Li, Mei; Wang, Jianan; Jing, Ruochen (Frontiers in Psychology, 2022)
Background: Self-efficacy was considered as a promising target for self-management of symptoms for adolescents with asthma. The measurement of self-efficacy in adolescents with asthma requires effective self-report tools, which has not been met at present. So the aim of this study was to cross-culturally validate the Adolescent Asthma Self-Efficacy Questionnaire (AASEQ). Methods: Four hundred and sixty-eight adolescents with asthma were invited to the psychometric properties test between July 2021 to June 2022.. We conducted confirmatory factor analysis to determine the structure of the AASEQ. The relationship between the AASEQ and General Self-Efficacy Scale was tested to evaluat the construct validity.The reliability was evaluated by retest reliability, internal consistency and inter-factor correlation. Results:Confirmatory factor analysis indicated a significantly good fit for a four-factor model, which explained 62.697% of the total variance. The fit indices of the four-factor model were acceptable, and standardized factor loading ranged from 0.631 to 0.880. The C-AASEQ showed acceptable internal consistency (Cronbach's α=0.810 to 0.927) and test-retest reliability (intraclass correlation coefficients=0.64 to 0.89). Content validity index at the scale level was 0.96, and content validity index at the item level was 0.86 to 1. Conclusion: The Chinese version of Adolescent Asthma Self-Efficacy Questionnaire showed consistently acceptable positive psychometric properties, and can be used as an instrument to assess self-efficacy of adolescents with asthma in China.